Critérios para o diagnóstico clínico de crianças respiradoras orais na atenção básica de saúde - Rubens Rafael Abreu (2013)
Oral breathing has a high prevalence in children, but the etiological diagnosis is limited by difficult access to complementary exams. This study aimed to determine criteria for clinical diagnosis, in the primary level of health care, of oral breathing in children between two and 13 years old, residents of Cedro do Abaeté MG. Its a population study with sample constituted by the totality of the target population. Were part of the study 221 children residing in the town, whose population is composed by 1,203 inhabitants. Those responsible for the children answered a social-economic-environmental questionnaire. The children were led to the interview and pediatrics examination directed to the diagnosis of oral breathing, and nasal endoscopy, allergic skin test and cavum radiography were requested. Since 19 children (8.6%) didn´t complete all solicited exams, the sample was made of 202 children (91.4%). The data were analyzed with the SPSS program, 10.5 version. P-value, sensitivity, specificity, positive predictive value, negative predictive value, ROC curve and kappa test were determined. The latter aimed to evaluate the concordance between nasal endoscopy and clinical examination regarding hypertrophy of nasal turbinates (75.75%), tonsilar hypertrophy (81.6%) and nasal septum obstructive deviation (91.7%). Most children were male (52.0%), with a mean age of 8.4 years. The prevalence of oral breathing was 59.4%. The main clinical manifestations frequency, sensitivity and PPV were, in percentage: nasal obstruction 64.1, 68.67 and 76.87, itching nose 61.4, 67.33 and 81.45, sleeping with open mouth 54.0, 57.33 and 78.90, and snoring 49.5, 54.0 and 81.0. Regarding the main alterations found in the clinical examination, the numbers were: hypertrophy of nasal turbinates 84.2, 83.33 and 73.96, ogival palate 81.7, 82.0 and 74.55, non-sealing of the lips 52.0, 54.67 and 78.10, and thoracic alterations 44.1, 48.67 and 82.02. The main causes of oral breathing were: allergic rhinitis (68.8%), adenoid hypertrophy (18.8%), tonsilar hypertrophy (10.9%) and nasal septum obstructive deviation (6.9%), all of them with p-value < 0.001. The frequency of cleaning the house and time of use of the mattress were significant (p = 0.018 and 0.015 respectively). The diagnosis of oral breathing is clinical, and it is up to the pediatrician to perform anamnesis and a detailed clinical examination valuing the signs and symptoms for an early diagnosis.